Research on the Impact of New Quality Productivity on Enterprise Owners’ Equity—An Empirical Analysis Based on Chinese A-Share Listed Companies - Jin, Chen (Journal of Global Economy, Business and Finance, 2025)
Based on data from Chinese A-share listed companies from 2015 to 2023, this paper constructs a micro-level indicator of new quality productivity and uses a panel fixed effects model to test its impact on owners’ equity. The study finds that new quality productivity has a significant positive impact on owners’ equity: for every 1% increase in new quality productivity, the logarithm of owners’ equity increases by approximately 0.559%, and this growth is achieved through increased operating revenue and capitalizable R&D investment. Regional and industry heterogeneity tests show that the impact of new quality productivity on owners’ equity is most significant in western regions; the impact of new quality productivity on owners’ equity is also significant in non-heavily polluting enterprises. This study enriches the theoretical perspective on the relationship between technological factors and financial data, providing practical reference for enterprises to optimize technological investment and for regulatory authorities to improve innovation policies.